A Review on Factors Influencing Readiness for Change Management in Organisation - Hafis Ahmad, Mohd; Ismail, Syuhaida; Nurul Mardiah Wan Mohd Rani, Wan; Hussaini Wahab, Mohammad (International Journal of Engineering and Technology, 2018)
It is crucial for an organisation to understand employeesâ€™ readiness for the organisational change instead of focusing on resistance to change since it can be more useful for implementing effective human resource practices and organisation development interventions. Thus, this paper reviews the literature on employeesâ€™ readiness for change, particularly the factors that influence their readiness in the organisation. In this paper, the current organisation practices on change management is discussed before the concept of individual readiness for organisational change as well as its relationship with the four categories of antecedents, which are internal context, change content, process and individual attributes are reviewed. This paper also highlights some of the issues and research areas that can be considered for future studies in relation with change management in organisations.Â Â